1981
DOI: 10.1007/bf01976653
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of potato spindle tuber viroid by aphids

Abstract: Aulacorthum solani (Kaltenbach), Macrosiphum euphorbiae (Thomas) and Myzus persicae (Sulzer) were used for transmission experiments in laboratory and glasshouse. As inoculum served PSTV-containing tomato foliage and artificial diets containing purified PSTV. It is concluded that M. euphorbiae can transmit PSTV in a non-persistent way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…PSTVd was reported to be transmitted at low frequency in a nonpersistent manner by the aphid Macrosiphum euphorbiae (De Bokx and Pirone, 1981) and to be aphid transmitted to up to 100% of test plants from source plants in which it was in joint infection with PLRV (Salazar et al, 1995;Syller et al, 1997). However, in a detailed analysis of this transmission route, Singh and Kurz (1997) found only low rates of transmission (7%) in association with PLRV and, as mentioned in Chapter 12, Section III, D, 1, a, iv, there are some open questions concerning aphid transmission of viroids.…”
Section: Transmissionmentioning
confidence: 99%
“…PSTVd was reported to be transmitted at low frequency in a nonpersistent manner by the aphid Macrosiphum euphorbiae (De Bokx and Pirone, 1981) and to be aphid transmitted to up to 100% of test plants from source plants in which it was in joint infection with PLRV (Salazar et al, 1995;Syller et al, 1997). However, in a detailed analysis of this transmission route, Singh and Kurz (1997) found only low rates of transmission (7%) in association with PLRV and, as mentioned in Chapter 12, Section III, D, 1, a, iv, there are some open questions concerning aphid transmission of viroids.…”
Section: Transmissionmentioning
confidence: 99%
“…Early reports (Goss, 1930) suggested that PSTVd might be transmitted by chewing-insects, but these reports have not been confirmed. De Bokx & Piron (1981) reported a low rate of transmission by the aphid Macrosiphum euphorbiae (Thomas) but no transmission was obtained with either Myzus persicae (Sulz.) or Aulacorthum solani (Kaltenbach).…”
mentioning
confidence: 99%
“…All viroids are transmissible by grafting, while a number of reports are for transmission through seeds and pollen of the infected plants [3,55,65,71,72,73,87]. There are a few reports of transmission of pospiviroid by insects [10,21]. Despite the free RNA nature of viroids, PSTVd can survive in freeze-dried tomato leaves at room temperature for several years [66] or in true potato seeds for over 20 years [72].…”
Section: Viroid a Novel Phytopathogenmentioning
confidence: 99%